7 - The Roles of Higher Education in the Democratization of Politics in Africa: Survey Reports from HERANA - Robert Mattes,; Thierry M. Luescher-Mamashela, (Journal of Higher Education in Africa, 2012)
Against the theory on the nexus of higher education and citizenship, this article brings together the main findings and conclusions of three related studies with African mass publics, parliamentarians from African legisla- tures, and students from three African flagship universities, conducted by the Higher Education Research and Advocacy Network in Africa (HERANA). The article shows that higher education provides advantages in various measures of democratic citizenship and leadership. It plays important roles with regard to access to political information, information gathering skills, and levels of political knowledge; the ability to offer opinions and critical perspectives on politics and the economy; and levels of democratic values and democratic action. Moreover, university-educated MPs seem to make much better sense of the unique complexities of legislatures and their mul- tiple competing functions than their less educated peers. This might reflect the knowledge and analytic skills acquired through higher education, the fact that universities are themselves highly complex institutions that they needed to negotiate as students, and the finding that students acquire ex- tensive organisational leadership experience while at university. In light of this, the article suggests that higher education can play a crucial role in the democratisation of politics in Africa by developing “institution-builders” for state and civil society.